Operando reduction of elastic modulus in (Pr, Ce)O2−δ thin films. (15th February 2016) - Swallow, Jessica G.; Kim, Jae Jin; Kabir, Mukul; Smith, James F.; Tuller, Harry L.; Bishop, Sean R.; Van Vliet, Krystyn J.
Abstract: Non-stoichiometric oxides are key functional materials within technologies such as solid oxide fuel cells (SOFCs) and gas sensors that often exhibit interdependent electrochemical and mechanical properties affecting operando mechanical stability. Here, we explore this electrochemomechanical coupling experimentally and computationally for (Pr, Ce)O2− δ (PCO), a model SOFC cathode material. We quantified Young's elastic modulus E of PCO thin films in situ, at temperatures up to 600 ∘ C and oxygen partial pressures pO2 down to 10 −3 atm via environmentally controlled nanoindentation. The observed significant reduction (up to 40%) in E with increased temperature or decreased pO2 correlated with changes in oxygen vacancy concentration δ and lattice parameter a expected due to chemical expansion. We confirmed the trend of decreased E with increased δ and a via first principles calculations for bulk PCO. The experimentally observed decrease in E vs. pO2 and temperature was more extreme than predicted by bulk computations, and is anticipated from the higher concentration of vacancies in thin films relative to bulk. These results demonstrate that accurate models of deformation in thin-film devices comprising these chemomechanically coupled oxides may differ markedly from bulk counterparts, and must reflect significant, reversible decreases in elastic moduli resulting from increased temperature and decreased pO2 . Graphical abstract: